2021
DOI: 10.5788/31-1-1635
|View full text |Cite
|
Sign up to set email alerts
|

Problems in Defining Ethnicity Terms in Dictionaries

Abstract: Despite the fact that lexicographers have increasingly been taking more care when it comes to defining socially sensitive terms, we argue that ethnicity terms still remain rather poorly defined. In a number of online monolingual dictionaries we surveyed in this study, we find that ethnicity terms are generally simplistically defined, mostly in terms of geography and citizenship, and argue that such definitions are too reductionist and sometimes even erroneous. We also find that some disparaging ethnicity terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Like in Henderson's study (2003), this reference tool records the highest number of terms, 69% of which are described as offensive through the use of labels, definitions, usage notes, or a combination of these sections. Žugić and Vuković-Stamatović (2021) present a study based on the qualitative multilingual analysis of the definition of one single lemma, namely the word for Albanian, in nineteen online and freely accessible monolingual dictionaries. As to English, the authors investigate only three general-purpose works including the Merriam-Webster.com dictionary site (2020), The Random House Unabridged Dictionary hosted on the Dictionary.com site (2020) and The American Heritage Dictionary of the English Language (2020) hosted on Thefreedictionary.com site.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Like in Henderson's study (2003), this reference tool records the highest number of terms, 69% of which are described as offensive through the use of labels, definitions, usage notes, or a combination of these sections. Žugić and Vuković-Stamatović (2021) present a study based on the qualitative multilingual analysis of the definition of one single lemma, namely the word for Albanian, in nineteen online and freely accessible monolingual dictionaries. As to English, the authors investigate only three general-purpose works including the Merriam-Webster.com dictionary site (2020), The Random House Unabridged Dictionary hosted on the Dictionary.com site (2020) and The American Heritage Dictionary of the English Language (2020) hosted on Thefreedictionary.com site.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Furthermore, and more relevantly for this article, very few studies have observed general-purpose online dictionaries, at least to an extent and they have highlighted different aspects of the English language of ethnic conflict (cf. Henderson 2003, Nissinen 2015, Žugić and Vuković-Stamatović 2021.…”
mentioning
confidence: 99%
“…According to the research, the OEDO proved to be the dictionary which records the highest number of ethnophaulisms (35 out of 37), whose offensiveness is indicated in 69% of instances through the use of labels, definitions, usage notes, or a combination of these sections (Nissinen 2015: 56-57). Of a different nature is the research carried out by Žugić and Vuković-Stamatović (2021), which concentrates on the qualitative analysis of the definition of one single lemma, namely the word for Albanian, in a group of 19 online and freely accessible monolingual dictionaries of multiple languages. As concerns English, as the authors explain (2021: 183-185), these mostly include learner's dictionaries and only three general-purpose works comprising the Merriam-Webster.com dictionary site (2020), The Random House Unabridged Dictionary hosted on the Dictionary.com site (2020) and The American Heritage Dictionary of the English Language (2020) hosted on Thefreedictionary.com site.…”
mentioning
confidence: 99%